Competition between microtubule-associated proteins directs motor transport - Brigette Y. Monroy (Nature Portfolio, 2018)
Motor and non-motor microtubule-associated proteins (MAPs) bind to the microtubule lattice, but it is unclear how their binding activities are coordinated and how this impacts motor transport. Here the authors show how MAP competition controls microtubule access to determine the distribution and balance of motor activity.